Effect of nanosilica on foam and thermal stability of a foam extinguishing agent. Issue 2 (2nd October 2017) - Tang, Baohua; Wu, Zhaoliang; Chen, Wei-hong
Abstract : This paper presents a study of the effect of the size of silica powder on the foaming capability and thermal stability of a foam extinguishing agent using 15 nm, 30 nm and 4 μm silica powders. Its effect on the superficial morphology of the foam was also studied. The results indicate that the decrease in the size of silica powder reduced the foaming capability of the foam extinguishing agent, but increased the thermal stability of the foam. With the 15 nm silica powder, the foaming capability decreased by 20·1%; the 25% drainage time, by 257%; the 50% drainage time, by 122%; and the thermal stability, by 139%. The superficial morphology images of the foams demonstrate that the nanosilica powders were more readily adsorbed at the gas–liquid interface to increase the lamella thickness and slow down film drainage. As a result, the powders, particularly the 15 nm silica powder, greatly improved the foam stability.